Analysis of Police Investigation Interviews in Defamation Cases: A Forensic Linguistics Perspective - Sholihatin, Endang; Sukirmiyadi, Sukirmiyadi; Haryono, Nanang (Journal of Languages and Language Teaching, 2024)
Police interviews with suspects often face criticism due to distortions in the preparation of examination reports. These distortions arise from a lack of understanding of the basic linguistic principles governing oral discourse production and the differences between spoken and written language. This study addresses the following research questions: (a) What is the structure of interrogative sentences?; (b) What strategies are employed in the formulation of interrogative sentences?; (c) How are investigative interview questions classified? The objectives of this study are to elucidate: (a) the structure of interrogative sentences; (b) strategies for formulating interrogative sentences; (c) the classification of investigative interview questions. This qualitative study utilizes a case study approach. Primary data sources include interviews with five police investigators from the East Java Regional Police and secondary data from ten examination reports in defamation cases from local police departments in East Java, Indonesia. Primary data were collected using semi-structured interview techniques. The study employs an interactive model of qualitative data analysis. This research reveals: (a) clear, precise, logical, and unambiguous sentence structures that enable suspects to provide complete and structured information; (b) current strategies used by investigators in information elicitation, utilizing the SI-A-DI DE-MEN BA-BI model; (c) the classification of police investigative interview questions into broad open-ended questions and narrow open-ended questions. The application of forensic linguistics techniques in police investigative interviews contributes new insights by developing adaptive and contextual interview methods. These methods effectively and accurately elicit information related to defamation cases, promoting justice in legal processes.